Asymptotic Behavior of Solutions of the Cauchy Problem x′ = f(t, x, x′), x(0) = 0
We prove the existence of continuously differentiable solutions \(x:(0,ρ ] → R^n\) such that \| x( t ) - ξ ( t ) \| = O( η ( t )